Technology Updates on Plate Bending Machines with Hydraulic Systems - Amrullah, Amrullah; Muttaqin, Ahmad Nurul; Mihdar, Uswatul Hasanah (Universitas Muhammadiyah Yogyakarta, 2024)
The swift progression of industrial technology has profoundly influenced the manufacturing sector, especially in the domain of sheet metal manipulation. Hydraulic plate bending machines hold a pivotal role in contemporary production due to their precision in shaping sheet metal components. This study aims to elevate the versatility and efficiency of hydraulic plate bending machines through innovative modifications. Key components underwent substantial alterations, including punch substitution, installation of dual punch locking plates, and integration of a pressure gauge. An evaluation ensued to determine the optimal parameters duration and force requisite for bending sheet metals ranging from 1 mm to 4 mm in thickness, aimed at assessing machinery efficacy. Test outcomes unveiled the modified machine's adeptness in accurately bending sheets of varying thicknesses, affirming its intended functionality. Moreover, the machine's enhanced adaptability allowed for seamless interchangeability of punches with diverse sizes and shapes. These empirical findings provide invaluable insights for enterprises striving to streamline manufacturing processes and boost overall productivity. Notably, this study highlights the pivotal role of technological advances in hydraulic plate bending machines, offering firms an efficient avenue to cater to diverse sheet metal shaping demands, thereby amplifying productivity and adaptability in industrial operations.